A method for improving the high temperature stability of sintered silver porous structure and a method for preparing key materials

By introducing metal salt into the silver paste to modify the surface of silver powder, the problem of structural changes in the porous structure of sintered silver in high-temperature environment is solved, the high-temperature stability and safety are improved, and the application scope of sintered silver technology is expanded.

CN117182065BActive Publication Date: 2025-05-02JIANGNAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202311162429.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-05-02
Estimated Expiration
2043-09-08

AI Technical Summary

Technical Problem

The structural changes of the sintered silver porous structure in a long-term high-temperature environment lead to uneven heat dissipation of the chip, reduced connection strength and reduced overall reliability, which poses safety hazards.

Method used

By introducing metal salt into the silver paste, the surface of the silver powder is modified to ensure that the metal salt is evenly dispersed in the silver paste, the sintering efficiency is improved, and the changes in the porous structure of the sintered silver are suppressed in a high-temperature environment.

Benefits of technology

It effectively improves the high temperature stability of the porous structure of sintered silver, inhibits structural changes and the generation of silver nanowires, reduces safety risks, and expands the application scope of sintered silver technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117182065B_ABST
    Figure CN117182065B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for improving the high-temperature stability of a sintered silver porous structure and a method for preparing key materials. The key material of the present invention is a silver-based solder paste, and the preparation method thereof is as follows: first, a metal salt solution is prepared; then, silver powder is added to the metal salt solution, and stirred to obtain a mixed solution; after the mixed solution is heated and dried, it is cooled to room temperature to obtain a metal salt-modified silver powder, which is mixed with an organic solvent II to obtain a silver paste primary product, and stirred and homogenized to obtain a silver-based solder paste. The present invention improves the uniformity of the dispersion of the metal salt in the silver paste and the silver sintering efficiency by modifying the surface of the silver powder with a metal salt; at the same time, the metal and its oxide with high cohesive energy obtained by decomposing the metal salt can inhibit the changes in the porous structure of the sintered silver during high-temperature aging, and improve the high-temperature stability of the sintered silver porous structure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of silver sintering interconnection of high-power chip mounting materials, and in particular to a method for improving the high-temperature stability of a sintered silver porous structure and a method for preparing key materials. Background Art

[0002] Sintered silver materials are considered to be ideal materials for high-power semiconductor chip mounting due to their excellent electrical and thermal conductivity and the ability to connect at low temperatures and serve at high temperatures. High-power semiconductors usually generate a lot of heat when they are in operation, which causes the mounting materials and the chip-substrate connection structure to be at high ambient temperatures for a long time, which places extremely high demands on the high-temperature thermal stability of the mounting materials. However, sintered silver itself presents a porous structure. When it is in a high-temperature environment for a long time, its porous structural characteristics will continue to change due to secondary sintering (aging): although the overall porosity hardly changes, a large number of small-sized pores will gradually gather and eventually form a small number of large-sized pores. This change will not only lead to uneven heat dissipation of the chip but also reduce the chip connection strength; at the same time, this change in the porous structure is likely to reduce the overall reliability of the power semiconductor device, causing great safety hazards. In summary, the structural changes of the sintered silver porous structure in a long-term high-temperature environment will seriously reduce its reliability as a high-temperature mounting material (especially when the mounting size is very small), limiting its application in some semiconductor devices that require long-term high-temperature operation.

[0003] In addition, when the sintered body is in a high-temperature environment for a long time, due to the influence of stress, a large number of silver nanowires will be generated on the surface. Although the silver nanowires have no obvious effect on the conductivity of the circuit, for the more sophisticated microcircuits in the future, the silver nanowires produced by adjacent circuits are very likely to come into contact with each other and cause a short circuit, resulting in failure of the entire device.

[0004] In order to improve the high temperature stability of the sintered silver porous structure, studies have shown that a small amount of nanoparticles such as WO3, Nb2O5, and AlN can be added to the silver paste. After sintering, these nanoparticles can be dispersed in the sintered silver porous structure. Because these particles have high cohesion and can also connect with silver, these nanoparticles can improve the high temperature thermal stability of the sintered silver porous structure.

[0005] However, there are several disadvantages in directly adding nanoparticles such as WO3, Nb2O5, AlN, etc. to the silver paste: First, because the nanoparticles have high surface energy and are easily agglomerated together, it is difficult to ensure that the nanoparticles such as WO3, Nb2O5, AlN, etc. are evenly dispersed in the silver paste; second, nanoparticles such as WO3, Nb2O5, AlN, etc. are non-metallic, which will reduce the electrical and thermal conductivity of sintered silver; third, there is a significant difference in surface charge between the nanoparticles such as WO3, Nb2O5, AlN, etc. and the silver particles or silver flakes in the silver paste, and phase separation may occur during long-term storage, reducing the stability of the silver paste. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention provides a method for improving the high temperature stability of a sintered silver porous structure and a method for preparing key materials. The present invention can ensure the uniformity of the dispersion of the metal salt in the silver paste by modifying the surface of the silver powder with a metal salt (instead of directly adding metal salt particles), thereby improving the silver sintering efficiency and reducing the influence of the thickness of the metal oxide formed during the high temperature aging process on the electrical and thermal conductivity of the sintered silver porous structure.

[0007] The technical solution of the present invention is as follows:

[0008] A method for preparing a silver-based solder paste comprises the following steps:

[0009] S1: preparing a metal salt solution;

[0010] S2: adding silver powder to the metal salt solution prepared in step S1, and stirring to obtain a mixed solution;

[0011] S3: heating the mixed solution to dryness, and then cooling it to room temperature to obtain metal salt modified silver powder;

[0012] S4: mixing the metal salt modified silver powder obtained in step S3 with organic solvent II to obtain a primary product of silver paste;

[0013] S5: Stir and homogenize the initial silver paste product to obtain a silver-based solder paste.

[0014] In one embodiment, in step S1, the metal salt solution is obtained by dissolving a metal salt in an organic solvent I; the metal salt includes one or more of a nickel salt and a copper salt.

[0015] In one embodiment, the nickel salt includes nickel formate, nickel acetate, nickel carbonate, and nickel oxalate; the copper salt includes copper formate, copper acetate, copper carbonate, and copper oxalate; the amount of the organic solvent I added is an amount that allows the metal salt to be fully dissolved; and the organic solvent I is anhydrous ethanol.

[0016] In one embodiment, in step S2, the mass ratio of the silver powder to the metal salt is 10:0.1-1.5.

[0017] In one embodiment, in step S3, the heating and drying is performed at a temperature of 50-70° C. for 3-5 hours.

[0018] In one embodiment, in step S4, the mass ratio of the metal salt modified silver powder to the organic solvent II is 9-10:1-1.5; the organic solvent II includes one or more of ethylene glycol, α-terpineol, n-butanol, dipropylene glycol methyl ether acetate, glycerol, 1,2-propylene glycol, diethylene glycol diethyl ether, 2-amino-2-methyl-1-propanol, and 2-ethylhexylamine.

[0019] In one embodiment, in step S5, the stirring is mechanical stirring or planetary stirring, the stirring speed is 1800-2000r / min, and the time is 10-20min; the homogenization is three-roll mill grinding homogenization, the roller gap is 3-5μm, the roller speed is 200-300r / min, and the grinding time is 20-30min.

[0020] A silver-based solder paste prepared by the preparation method.

[0021] The silver-based solder paste is used to prepare a sintered silver porous structure, and the porosity of the porous structure is between 3% and 20%.

[0022] A detection method for improving the high temperature stability of a sintered silver porous structure comprises the following steps:

[0023] (1) preparing a silver-based solder paste according to the preparation method;

[0024] (2) After printing the silver-based solder paste prepared in step (1) on the substrate, place the chip to form a sandwich structure, heat it to 200-300° C. at a heating rate of 10-30° C. / min, and sinter for 30-60 minutes to form a joint.

[0025] (3) Printing the silver-based solder paste prepared in step (1) on a substrate to form a pattern, heating the substrate to 200-300° C. at a heating rate of 10-30° C. / min, sintering the substrate for 30-60 min to form a circuit, and then performing a resistivity test at room temperature using a ST2263 four-point probe tester from Suzhou Jingge Electronics Co., Ltd., and performing microstructure observation at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0026] (4) After the circuit obtained in step (3) was stored at 200° C. for 100 h, the microstructure was observed again at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0027] The beneficial technical effects of the present invention are:

[0028] In order to improve the high-temperature stability of the sintered silver porous structure, the present invention introduces metal salts into the silver paste. During the sintering process of the silver paste, the metal salts will decompose to produce pure metals or metal oxides. Due to the heterogeneous nucleation mechanism, these metals or oxides will preferentially cover the surface of the silver powder. Compared with the silver element, the introduced metal and the oxide formed during the high-temperature aging process have higher cohesive energy, which can effectively inhibit the changes in the sintered silver porous structure in a high-temperature environment.

[0029] In order to ensure that the metal salt is evenly dispersed in the silver paste, the present invention first fully dissolves the metal salt in an organic solvent, then adds silver powder to the solution and stirs it thoroughly, and finally evaporates the solvent at a low temperature to promote the precipitation of the metal salt on the surface of the silver powder. Through the process of dissolving and precipitating the metal salt, fine metal salts can be precipitated on the surface of the silver powder to achieve metal salt-modified silver powder. Compared with large particles of metal salt directly in the silver paste, the dissolution-precipitation method of the present invention can ensure that the silver powder and the metal salt are fully mixed and uniform, which is conducive to the introduction of metals and their oxides to play a role in the sintered silver structure.

[0030] Based on the above principles and methods, the content of the metal and its oxide introduced in the present invention can be precisely controlled, and the content of the added metal salt can be low, which has little effect on the electrical and thermal conductivity and mechanical strength of the sintered silver itself; it has good dispersibility and good inhibition of changes in the porous structure of the sintered silver.

[0031] The principle and method provided by the present invention are highly applicable. Whether it is micron silver paste, submicron silver paste, nano silver paste or multi-peak mixed silver paste, this method can theoretically be used to improve it, and the high-temperature stability of the sintered silver porous structure can be effectively improved.

[0032] The reagents used in the present invention are all non-toxic and colorless, and only a few reagents have a certain odor, which will not cause harm to human health and will not pollute the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is Example 1 of the present invention: silver sintered porous structure (sintering process: sintering at 250° C. for 30 minutes).

[0034] Figure 2 This is Example 1 of the present invention: a sintered silver porous structure after high-temperature aging at 200° C. for 100 hours.

[0035] Figure 3 This is Example 2 of the present invention: silver sintered porous structure (sintering process: sintering at 250° C. for 30 min).

[0036] Figure 4 This is Example 2 of the present invention: a sintered silver porous structure after high-temperature aging at 200° C. for 100 hours.

[0037] Figure 5 This is comparative example 1 of the present invention: silver sintered porous structure (sintering process: sintering at 250° C. for 30 min).

[0038] Figure 6 This is comparative example 1 of the present invention: a sintered silver porous structure after high-temperature aging at 200° C. for 100 hours.

[0039] Figure 7 Schematic diagram of the silver connector of the present invention.

[0040] Figure 8 Schematic diagram of the printed silver circuit of the present invention. DETAILED DESCRIPTION

[0041] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.

[0042] A method for preparing a silver-based solder paste comprises the following steps:

[0043] S1: preparing a metal salt solution;

[0044] S2: adding silver powder to the metal salt solution prepared in step S1, and stirring to obtain a mixed solution;

[0045] S3: heating the mixed solution to dryness, and then cooling it to room temperature to obtain metal salt modified silver powder;

[0046] S4: mixing the metal salt modified silver powder obtained in step S3 with organic solvent II to obtain a primary product of silver paste;

[0047] S5: Stir and homogenize the initial silver paste product to obtain a silver-based solder paste.

[0048] In one embodiment of the present invention, in step S1, in order to evenly disperse the metal salt on the surface of the silver powder, the metal salt is added to the silver powder in the form of a metal salt solution, and the metal salt solution is obtained by dissolving the metal salt in an organic solvent I; the metal salt includes one or more of nickel salt and copper salt.

[0049] In one embodiment of the present invention, the nickel salt includes nickel formate, nickel acetate, nickel carbonate, and nickel oxalate; the copper salt includes copper formate, copper acetate, copper carbonate, and copper oxalate; and the amount of the organic solvent I added is an amount that allows the metal salt to be fully dissolved. Preferably, the nickel salt is nickel formate dihydrate, and the copper formate is copper formate tetrahydrate.

[0050] In one embodiment of the present invention, the silver powder used may be one or a combination of micron silver flakes (1-5 μm), submicron silver particles (101-999 nm), and nano silver particles (100 nm and below) in a certain proportion.

[0051] In one embodiment of the present invention, in order to ensure a more reasonable relative distribution of silver powder and metal salt, in step S2, the mass ratio of the silver powder to the metal salt is 10:0.1, 10:0.5, 10:1.0 or 10:1.5.

[0052] In one embodiment of the present invention, in step S3, the heating and drying temperature is 50°C, 60°C, 65°C or 70°C, and the time is 3h, 4h or 5h.

[0053] In one embodiment of the present invention, the relative amounts of metal salt-modified silver powder and organic solvent II are studied, that is, in step S4, the mass ratio of the metal salt-modified silver powder to the organic solvent II is 9:1, 10:1, 9:1.5, 9.5:1, 9.5:1.5 or 10:1.5; the organic solvent II includes one or more of ethylene glycol, α-pinene alcohol, n-butanol, dipropylene glycol methyl ether acetate, glycerol, 1,2-propylene glycol, diethylene glycol diethyl ether, 2-amino-2-methyl-1-propanol, and 2-ethylhexylamine.

[0054] In one embodiment of the present invention, in step S5, the stirring is mechanical stirring or planetary stirring, the stirring speed is 1800r / min, 1900r / min or 2000r / min, and the time is 10min, 15min or 20min; the homogenization is three-roll mill grinding homogenization, the roller gap is 3-5μm, the roller speed is 200r / min, 250r / min or 300r / min, and the grinding time is 20min, 25min or 30min.

[0055] A silver-based solder paste prepared by any of the above methods, the silver paste has high-temperature stability, the metal salt in the silver paste will preferentially decompose during sintering to produce pure metal or metal oxide, the metal or metal oxide covers the surface of the silver powder, has high cohesive energy, can effectively prevent the change of the porous structure of the sintered silver under high-temperature environment, and the metal salt is evenly dispersed on the surface of the solder paste.

[0056] The silver-based solder paste is used to prepare a sintered silver porous structure, and the porosity of the porous structure is 3-20%.

[0057] In one embodiment of the present invention, a detection method for improving the high temperature stability of a sintered silver porous structure is also provided, comprising the following steps:

[0058] (1) Prepare a silver-based solder paste according to the above preparation method.

[0059] (2) After printing the silver-based solder paste prepared in step (1) on the substrate, place the chip to form a sandwich structure, heat the substrate to 200° C., 250° C. or 300° C. at a heating rate of 10° C. / min, 20° C. / min or 30° C. / min, and sinter for 30 min, 45 min or 60 min to form a joint.

[0060] (3) Printing the silver-based solder paste prepared in step (1) on a substrate to form a pattern, heating the substrate to 200°C, 250°C or 300°C at a heating rate of 10°C / min, 20°C or 30°C / min, sintering the substrate for 30 min, 45 min or 60 min to form a circuit, and then performing a resistivity test at room temperature using a ST2263 four-point probe tester from Suzhou Jingge Electronics Co., Ltd., and performing microstructure observation at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0061] (4) After the circuit obtained in step (3) was stored at 200° C. for 100 h, the microstructure was observed again at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0062] Example 1

[0063] A silver-based solder paste, the preparation method of which comprises the following steps:

[0064] S1: Prepare nickel formate dihydrate solution by adding 0.1 g of nickel formate dihydrate to anhydrous ethanol to fully dissolve the nickel formate dihydrate;

[0065] S2 then put 3 g of micron silver flake powder and 7 g of submicron silver powder into the nickel formate dihydrate solution, and stirred magnetically for 2 h to obtain a mixed solution;

[0066] S3: then heating the mixed solution on a heating table at 50° C. for 5 h until the solvent is completely evaporated, and cooling to room temperature to obtain dry silver powder, i.e., metal salt-modified silver powder;

[0067] S4: Add 20% of dipropylene glycol methyl ether acetate and 80% of α-terpineol into a sample bottle to form a mixed solvent. Add the dried metal salt-modified silver powder into the sample bottle to prepare a silver paste (initial silver paste product); wherein the mass ratio of the silver powder to the solvent is 9:1.5;

[0068] S5: Use a glass rod to manually mix the silver paste evenly, put it into a planetary mixer, and stir it at 2000r / min for 20 minutes. Take out the silver paste from the planetary mixer, put it into a three-roll mill for grinding, dispersion and homogenization to obtain a silver-based solder paste, with a roller gap of 4μm, a roller speed of 250r / min, and a grinding time of 15min.

[0069] S6: After printing the prepared silver-based solder paste on the substrate, place the chip to form a sandwich structure, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a joint; print the prepared silver-based solder paste on the substrate to form a pattern, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a circuit.

[0070] S7: The resistivity of the circuit obtained in S6 was tested at room temperature using a ST2263 four-point probe tester from Suzhou Jingge Electronics Co., Ltd., and its microstructure was observed at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0071] S8: After the circuit obtained in S6 was aged at 200°C for 100 h, the microstructure was observed again at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0072] Example 2

[0073] A silver-based solder paste, the preparation method of which comprises the following steps:

[0074] S1: Prepare a nickel formate solution by adding 1.5 g of nickel formate to anhydrous ethanol to fully dissolve the nickel formate;

[0075] S2: Then, 6 g of micron silver flake powder and 4 g of submicron silver powder were added to the solution, and magnetic stirring was performed for 2 h to obtain a mixed solution;

[0076] S3: then heating the mixed solution at 60° C. on a heating table for 4 h until the solvent is completely evaporated, and cooling to room temperature to obtain dry silver powder, i.e., metal salt-modified silver powder;

[0077] S4: Add 80% of diethylene glycol diethyl ether and 20% of α-pinene alcohol into a sample bottle to form a mixed solvent. Add the dried metal salt-modified silver powder into the sample bottle to prepare a silver paste (initial silver paste product); wherein the mass ratio of the silver powder to the solvent is 10:1;

[0078] S5: Use a glass rod to manually mix the silver paste evenly, put it into a planetary mixer, and stir it at 1900r / min for 20 minutes. Take out the silver paste from the planetary mixer, put it into a three-roll mill for grinding, dispersion and homogenization to obtain a silver-based solder paste, with a roller gap of 5μm, a roller speed of 300r / min, and a grinding time of 20min.

[0079] S6: After printing the prepared silver-based solder paste on the substrate, place the chip to form a sandwich structure, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a joint; print the prepared silver-based solder paste on the substrate to form a pattern, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a circuit.

[0080] S7: The resistivity of the circuit obtained in S6 was tested at room temperature using a ST2263 four-point probe tester from Suzhou Jingge Electronics Co., Ltd., and its microstructure was observed at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0081] S8: After the circuit obtained in S6 was aged at 200°C for 100 h, the microstructure was observed again at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0082] Example 3

[0083] A silver-based solder paste, the preparation method of which comprises the following steps:

[0084] S1: Prepare a copper formate solution by adding 1 gram of copper formate to anhydrous ethanol to fully dissolve the copper formate;

[0085] S2: Then, 3 g of micron silver flake powder and 7 g of submicron silver powder were added to the solution, and magnetic stirring was performed for 2 h to obtain a mixed solution;

[0086] S3: The mixed solution is then heated on a heating table at 70°C for 3 h until the solvent is completely evaporated, and then cooled to room temperature to obtain dry silver powder;

[0087] S4: Add dipropylene glycol methyl ether acetate to the sample bottle to form a mixed solvent. Add the dried metal salt-modified silver powder to the sample bottle to prepare a silver paste (silver paste initial product); wherein the mass ratio of the silver powder to the solvent is 10:1;

[0088] S5: Use a glass rod to manually mix the silver paste evenly, put it into a planetary mixer, and stir it at 1800r / min for 20 minutes. Take out the silver paste from the planetary mixer, put it into a three-roll mill for grinding, dispersion and homogenization to obtain a silver-based solder paste, with a roller gap of 3μm, a roller speed of 200r / min, and a grinding time of 10min.

[0089] S6: After printing the prepared silver-based solder paste on the substrate, place the chip to form a sandwich structure, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a joint; print the prepared silver-based solder paste on the substrate to form a pattern, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a circuit.

[0090] S7: The resistivity of the circuit obtained in S6 was tested at room temperature using a ST2263 four-point probe tester from Suzhou Jingge Electronics Co., Ltd., and its microstructure was observed at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0091] S8: After the circuit obtained in S6 was aged at 200°C for 100 h, the microstructure was observed again at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0092] Comparative Example 1

[0093] A silver-based solder paste, the preparation method of which comprises the following steps:

[0094] S1: Prepare nickel formate solution by adding 0 g of nickel formate to anhydrous ethanol;

[0095] S2. Add 3 g of micron silver flake powder and 7 g of submicron silver powder into the solution and stir magnetically for 2 h to obtain a mixed solution.

[0096] S3 then heats the mixed solution on a heating table at 60° C. for 4 h until the solvent is completely evaporated to obtain dry silver powder;

[0097] S4: adding 20% ​​of dipropylene glycol methyl ether acetate and 80% of α-pineneol into a sample bottle to form a mixed solvent, and adding the dried metal salt-modified silver powder into the sample bottle to prepare a silver paste (initial silver paste product); wherein the mass ratio of the silver powder to the solvent is 9:1.5;

[0098] S5 manually mixes the silver paste with a glass rod, puts it into a planetary mixer, and stirs it at 2000r / min for 20 minutes. Take out the silver paste from the planetary mixer and put it into a three-roll mill for grinding, dispersion and homogenization. The roller gap is 5μm, the roller speed is 300r / min, and the grinding time is 20min.

[0099] S6: After printing the prepared silver-based solder paste on the substrate, place the chip to form a sandwich structure, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a joint; print the prepared silver-based solder paste on the substrate to form a pattern, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a circuit.

[0100] S7: The resistivity of the circuit obtained in S6 was tested at room temperature using a ST2263 four-point probe tester from Suzhou Jingge Electronics Co., Ltd., and its microstructure was observed at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0101] S8: After the circuit obtained in S6 was aged at 200°C for 100 h, the microstructure was observed again at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0102] Comparative Example 2

[0103] A silver-based solder paste, the preparation method of which comprises the following steps:

[0104] S1: Prepare nickel formate solution by adding 4 g of nickel formate to anhydrous ethanol;

[0105] S2. Add 3 g of micron silver flake powder and 7 g of submicron silver powder into the solution and stir magnetically for 2 h to obtain a mixed solution.

[0106] S3 then heats the mixed solution on a heating table at 60° C. for 4 h until the solvent is completely evaporated to obtain dry silver powder;

[0107] S4: 20% of dipropylene glycol methyl ether acetate and 80% of α-pinene alcohol are added into a sample bottle to form a mixed solvent. The dried metal salt-modified silver powder is added into the sample bottle to prepare a silver paste (initial silver paste product); wherein the mass ratio of the silver powder to the solvent is 9:1.5.

[0108] S5 manually mixes the silver paste with a glass rod, puts it into a planetary mixer, and stirs it at 2000r / min for 20 minutes. Take out the silver paste from the planetary mixer and put it into a three-roll mill for grinding, dispersion and homogenization. The roller gap is 5μm, the roller speed is 300r / min, and the grinding time is 20min.

[0109] S6: After printing the prepared silver-based solder paste on the substrate, place the chip to form a sandwich structure, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a joint; print the prepared silver-based solder paste on the substrate to form a pattern, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a circuit.

[0110] S7: The resistivity of the circuit obtained in S6 was tested at room temperature using a ST2263 four-point probe tester from Suzhou Jingge Electronics Co., Ltd., and its microstructure was observed at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0111] S8: After the circuit obtained in S6 was aged at 200°C for 100 h, the microstructure was observed again at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0112] Comparative Example 3

[0113] A silver-based solder paste, the preparation method of which comprises the following steps:

[0114] S1: Add dipropylene glycol methyl ether acetate into a sample bottle as a solvent, and directly add 1 gram of copper formate powder, 3 grams of unmodified micron silver flake silver powder, and 7 grams of unmodified submicron silver powder into the sample bottle to prepare a silver-copper solder paste; the mass ratio of the sum of the copper formate powder and the silver powder to the solvent is 10:1;

[0115] S2: Use a glass rod to manually mix the silver-based solder paste, put it into a planetary mixer, and stir it at 2000r / min for 20 minutes. Take out the silver paste from the planetary mixer and put it into a three-roll mill for grinding, dispersion and homogenization. The roller gap is 5μm, the roller speed is 300r / min, and the grinding time is 20min.

[0116] S3: After printing the prepared silver-based solder paste on the substrate, place the chip to form a sandwich structure, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a joint; print the prepared silver-based solder paste on the substrate to form a pattern, heat it to 250°C at a heating rate of 20°C / min, sinter it for 30 minutes, and form a circuit.

[0117] S4: The resistivity of the circuit obtained in S3 was tested at room temperature using a ST2263 four-point probe tester from Suzhou Jingge Electronics Co., Ltd., and its microstructure was observed at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0118] S5: After the circuit obtained in S3 was aged at 200°C for 100 h, the microstructure was observed again at room temperature using an EVO18 scanning electron microscope from Carl Zeiss AG.

[0119] Performance Testing

[0120] (1) Characterization of the stability of sintered silver porous structure:

[0121] The microstructure changes of the embodiment and comparative example 1 are as follows Figure 1-6 As shown in the figure, Figure 1 , 3 5 is the microstructure of Examples 1, 2 and Comparative Example 1 after sintering at 250° C. for 30 minutes. The porous structure surface is relatively flat, and no nanoparticles and nanowires exist. Figure 2 , 4, 6 are the surface microstructures after being kept warm at 200°C for 100h respectively. It can be seen that the microstructures of Examples 1 and 2 remain stable due to the presence of nickel. In obvious contrast, the microstructure of Comparative Example 1 changes greatly, the porous characteristics change, and a large number of nanowire structures appear on the surface, and there are also a large number of nanoparticles on the surface of the porous tissue, indicating that the porous structure stability of Comparative Example 1 is very poor.

[0122] In summary, through the observation of the porous structure of sintered silver, it can be found that the introduction of metal salts can effectively avoid the change of the porous structure of sintered silver during high-temperature aging, avoid the appearance of large pores, improve the reliability of the porous structure of sintered silver, and also inhibit the generation of silver nanowires, which eliminates the possibility of short circuit caused by mutual contact of silver nanowires generated in precision circuits working under high-temperature environment. In general, the addition of metal salts can reduce the safety hazards of sintered silver mounting materials in long-term high-temperature environment and expand the application scope of sintered silver technology.

[0123] (2) Conductivity and other performance tests

[0124] The resistivity test of the circuits prepared in the embodiment and the comparative examples was performed using the ST2263 four-point probe tester of Suzhou Jingge Electronics Co., Ltd. The results are shown in Table 1.

[0125] Table 1 Comparison of resistivity between examples and comparative examples

[0126] sample Resistivity (μΩ·cm) Example 1 9.09 Example 2 15.31 Implementation 3 10.06 Comparative Example 1 8.50 Comparative Example 2 100.21 Comparative Example 3 22.89

[0127] It can be seen from the above table that the content of the introduced metal salt and the degree of mixing uniformity have a significant effect on the conductivity. The increase in the content of metal salt in the silver paste will cause the conductivity of the sintered silver to decrease, and too much metal salt will significantly reduce the conductivity (Comparative Example 2). In addition, the uniformity of the metal salt in the silver paste also has a great influence on the conductivity. The silver paste components of Example 3 and Comparative Example 3 are exactly the same, but the method of introducing the metal salt into the silver paste is different. The three components directly mixed in Comparative Example 3 are difficult to mix uniformly, resulting in poor conductivity.

[0128] The present invention develops a method for improving the high temperature stability of a sintered silver porous structure and a method for preparing a key material. The material is composed of silver powder modified with metal salts and an organic solvent. During the sintering process, the metal salt on the surface of the silver powder will decompose to uniformly generate metal or oxide particles on the surface of the silver powder and sinter with the silver powder to form a porous silver structure. Since the metal produced by the metal salt will be locally oxidized to form a stable phase under a long period of high temperature, these stable phases are uniformly dispersed in the sintered silver porous structure, which can effectively hinder the diffusion of silver and improve the stability of the silver sintered porous structure. Compared with the existing direct addition of nanoparticles such as WO3, Nb2O5, AlN, etc., the present invention has the following advantages: first, the uniformity of the dispersion of the metal salt in the silver paste can be ensured by modifying the surface of the silver powder with metal salts (not directly adding metal salt particles); second, during the sintering process, the metal salt decomposes to generate metal or oxide particles, which helps to improve the silver sintering efficiency; third, the added metal salt content is small and the metal oxide (such as nickel oxide) formed during the high temperature aging process is very thin, which has little effect on the electrical and thermal conductivity of the sintered silver porous structure.

[0129] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.

Claims

1. A method for preparing a silver-based solder paste, characterized in that: The preparation method comprises the following steps: S1: preparing a metal salt solution; S2: adding silver powder to the metal salt solution prepared in step S1, and stirring to obtain a mixed solution; S3: heating the mixed solution to dryness, and then cooling it to room temperature to obtain metal salt modified silver powder; S4: mixing the metal salt modified silver powder obtained in step S3 with organic solvent II to obtain a primary product of silver paste; S5: stirring and homogenizing the initial silver paste product to obtain a silver-based solder paste; In step S2, the mass ratio of the silver powder to the metal salt is 10:0.1-1.

5.

2. The preparation method according to claim 1, characterized in that: In step S1, the metal salt solution is obtained by dissolving a metal salt in an organic solvent I; the metal salt includes one or more of a nickel salt and a copper salt.

3. The preparation method according to claim 2, characterized in that: The nickel salts include nickel formate, nickel acetate, nickel carbonate and nickel oxalate; the copper salts include copper formate, copper acetate, copper carbonate and copper oxalate; and the amount of the organic solvent I added is an amount sufficient to fully dissolve the metal salt.

4. The preparation method according to claim 1, characterized in that: In step S3, the heating and drying is performed at a temperature of 50-70° C. for 3-5 hours.

5. The preparation method according to claim 1, characterized in that: In step S4, the mass ratio of the metal salt modified silver powder to the organic solvent II is 9-10:1-1.

5.

6. The preparation method according to claim 1, characterized in that: In step S4, the organic solvent II includes one or more of ethylene glycol, α-terpineol, n-butanol, dipropylene glycol methyl ether acetate, glycerol, 1,2-propylene glycol, diethylene glycol diethyl ether, 2-amino-2-methyl-1-propanol, and 2-ethylhexylamine.

7. The preparation method according to claim 1, characterized in that: In step S5, the stirring is mechanical stirring or planetary stirring.

8. A silver-based solder paste prepared by the preparation method according to any one of claims 1 to 7.

9. A method for improving the high temperature stability of a sintered silver porous structure, characterized in that: The method comprises the following steps: (1) preparing a silver-based solder paste according to the preparation method according to any one of claims 1 to 7; (2) After printing the silver-based solder paste prepared in step (1) on the substrate, the chip is placed to form a sandwich structure, the temperature is increased to 200-300° C. at a heating rate of 10-30° C. / min, and sintered for 30-60 min to form a joint; (3) Printing the silver-based solder paste prepared in step (1) on a substrate to form a pattern, heating the substrate to 200-300° C. at a heating rate of 10-30° C. / min, and sintering the substrate for 30-60 min to form a circuit.

Citation Information

Patent Citations

  • Preparation method and interconnection process of carbon nanosphere (at) Ag core-shell material for low-temperature connection and high-temperature service

    CN116275028A

  • Surface-decorated silver powder and its producing method

    JP2001240901A

  • Ag-Ni-BASED ELECTRICAL CONTACT MATERIAL AND ITS MANUFACTURING METHOD

    JP2009030100A